Oligodendroglial TNFR2 Mediates Membrane TNF-Dependent Repair in Experimental Autoimmune Encephalomyelitis by Promoting Oligodendrocyte Differentiation and Remyelination - Madsen, Pernille M. (J Neurosci, 2016)
Tumor necrosis factor (TNF) is associated with the pathophysiology of various neurological disorders, including multiple sclerosis. It exists as a transmembrane form tmTNF, signaling via TNF receptor 2 (TNFR2) and TNFR1, and a soluble form, solTNF, signaling via TNFR1. Multiple sclerosis is associated with the detrimental effects of solTNF acting through TNFR1, while tmTNF promotes repair and remyelination. Here we demonstrate that oligodendroglial TNFR2 is a key mediator of tmTNF-dependent protection in experimental autoimmune encephalomyelitis (EAE). CNP-cre:TNFR2(fl/fl) mice with TNFR2 ablation in oligodendrocytes show exacerbation of the disease with increased axon and myelin pathology, reduced remyelination, and increased loss of oligodendrocyte precursor cells and mature oligodendrocytes. The clinical course of EAE is not improved by the solTNF inhibitor XPro1595 in CNP-cre:TNFR2(fl/fl) mice, indicating that for tmTNF to promote recovery TNFR2 in oligodendrocytes is required. We show that TNFR2 drives differentiation of oligodendrocyte precursor cells, but not proliferation or survival. TNFR2 ablation leads to dysregulated expression of microRNAs, among which are regulators of oligodendrocyte differentiation and inflammation, including miR-7a. Our data provide the first direct in vivo evidence that TNFR2 in oligodendrocytes is important for oligodendrocyte differentiation, thereby sustaining tmTNF-dependent repair in neuroimmune disease. Our studies identify TNFR2 in the CNS as a molecular target for the development of remyelinating agents, addressing the most pressing need in multiple sclerosis therapy nowadays. SIGNIFICANCE STATEMENT Our study, using novel TNF receptor 2 (TNFR2) conditional KO mice with selective TNFR2 ablation in oligodendrocytes, provides the first direct evidence that TNFR2 is an important signal for oligodendrocyte differentiation. Following activation by transmembrane TNF, TNFR2 initiates pathways that drive oligodendrocytes into a reparative mode contributing to remyelination following disease. This identifies TNFR2 as a new molecular target for the development of therapeutic agents in multiple sclerosis.